Green Accounting Terhadap Kinerja Keuangan Dengan Environmental Performance Sebagai Variabel Intervening - Nianty, Dara Ayu; Rachma, Nur; Susanti, Aulia; Nurfaulia, Nurfaulia (Jurnal Manajemen STIE Muhammadiyah Palopo, 2023)
Abstract This research focuses on the implementation of environmental accounting in companies, which mandates reporting environmental performance through channels such as annual reports, sustainability reports, websites, or other voluntary disclosures. The research objectives include evaluating the impact of environmental accounting on financial performance, assessing the impact on environmental performance, and identifying environmental performance as a mediator in the relationship between environmental accounting and financial performance. The study employs a quantitative method involving 14 companies in the plastic processing sector listed on the Indonesia Stock Exchange (BEI). Purposive sampling involves nine companies during the period 2018-2021, resulting in 36 data points from the annual financial reports of companies in the packaging and plastic subsector. Data analysis uses the Structural Equation Modelling (SEM) method with Partial Least Square (PLS) software. Research findings indicate that environmental accounting does not significantly impact financial performance, while it significantly influences environmental performance. Nevertheless, environmental performance affects financial performance, albeit not significantly as a mediator in the relationship between environmental accounting and financial performance. These results reflect the complex dynamics among variables in the context of the plastic processing industry on the BEI.Keywords: Green Accounting, Environmental Performance, Financial Performance.AbstrakPenelitian ini berfokus pada implementasi akuntansi lingkungan di perusahaan, yang mewajibkan pelaporan kinerja lingkungan melalui saluran seperti laporan tahunan, sustainability report, website, atau pengungkapan sukarela lainnya. Tujuan penelitian mencakup evaluasi dampak akuntansi lingkungan terhadap kinerja keuangan, penilaian dampak pada kinerja lingkungan, serta identifikasi kinerja lingkungan sebagai mediator dalam relasi antara akuntansi lingkungan dan kinerja keuangan. Penelitian ini menerapkan metode kuantitatif dengan melibatkan 14 perusahaan di sektor pengolahan plastik yang terdaftar di Bursa Efek Indonesia (BEI). Pengambilan sampel purposive melibatkan sembilan perusahaan selama periode 2018-2021, menghasilkan 36 data dari laporan keuangan tahunan perusahaan di subsektor kemasan dan plastik. Analisis data menggunakan metode Structural Equation Modelling (SEM) dengan software Partial Least Square (PLS). Temuan penelitian menunjukkan bahwa akuntansi lingkungan tidak berdampak signifikan terhadap kinerja keuangan, sementara berpengaruh signifikan terhadap kinerja lingkungan. Meskipun demikian, kinerja lingkungan memengaruhi kinerja keuangan, walaupun tidak signifikan sebagai mediator dalam hubungan antara akuntansi lingkungan dan kinerja keuangan. Hasil ini mencerminkan dinamika kompleks antar variabel dalam konteks industri pengolahan plastik di BEI.Kata Kunci: Green Accounting, Kinerja Lingkungan, Kinerja Keuangan.